1977
DOI: 10.1159/000127950
|View full text |Cite
|
Sign up to set email alerts
|

Early Biochemical and Hemodynamic Changes after Operation in a Bloodless Field

Abstract: Biochemical and hemodynamic changes during and after operation in a bloodless field have been investigated in 13 patients. The patients were athletes between the ages of 21 and 38 years who were healthy except for an inveterate ligament injury of the knee joint. Capillary blood flow in the tibialis anterior muscle was measured by the radioactive-Xenon-clearance technique. Fine plastic catheters for blood sampling were inserted into both femoral veins and into one radial artery. A significant increase in blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 8 publications
4
22
1
Order By: Relevance
“…When norepinephrine was added to the saline solution, there was a greater haemostatic effect compared with the saline solution alone. The efficacy of norepinephrine is related to the peak of blood flow that is normally present for 20 -30 min after tourniquet release [5]. The local infusion of norepinephrine before releasing the tourniquet induces contraction of peripheral vessels, with a reduction of this peak.…”
Section: Discussionmentioning
confidence: 99%
“…When norepinephrine was added to the saline solution, there was a greater haemostatic effect compared with the saline solution alone. The efficacy of norepinephrine is related to the peak of blood flow that is normally present for 20 -30 min after tourniquet release [5]. The local infusion of norepinephrine before releasing the tourniquet induces contraction of peripheral vessels, with a reduction of this peak.…”
Section: Discussionmentioning
confidence: 99%
“…After surgery, reactive blood flow increases, with the peak flow appearing within five minutes once the tourniquet is deflated (Larsson et al 1977). Most of the blood loss in TKA occurs during the first few postoperative hours.…”
Section: Effect Of Temporary Drain Clampingmentioning
confidence: 99%
“…Larsson et al noted back in the 1970's that when a tourniquet is released there is an increased reactive blood flow to the limb. 30 This effect was found to peak 5 minutes after tourniquet release, though persisted for several hours. Wakankar et al reported that this reactive hyperaemia can contribute to limb swelling and increased soft tissue tension after a tourniquet release, which in turn may explain the increased wound pain that this group of patients feel.…”
Section: Discussionmentioning
confidence: 97%